2022
DOI: 10.1080/15384047.2022.2088984
|View full text |Cite
|
Sign up to set email alerts
|

Clinical activity of 9-ING-41, a small molecule selective glycogen synthase kinase-3 beta (GSK-3β) inhibitor, in refractory adult T-Cell leukemia/lymphoma

Abstract: GSK-3β is a serine/threonine kinase implicated in tumorigenesis and chemotherapy resistance. GSK-3β blockade downregulates the NF-κB pathway, modulates immune cell PD-1 and tumor cell PD-L1 expression, and increases CD8 + T cell and NK cell function. We report a case of adult T-cell leukemia/lymphoma (ATLL) treated with 9-ING-41, a selective GSK-3β inhibitor in clinical development, who achieved a durable response. A 43-year-old male developed diffuse lymphadenopathy, and biopsy of axillary lymph node showed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 39 publications
0
6
0
1
Order By: Relevance
“…The case study reported here is from a patient in an ongoing clinical trial and provided rationale for this work, which indicates elraglusib’s potential utility in combination strategies with checkpoint blockade immunotherapy. In patients on this ongoing study, durable clinical responses to single-agent elraglusib have been observed, including in patients with refractory acute T cell leukaemia/lymphoma and malignant gliomas, with a favourable adverse event profile [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The case study reported here is from a patient in an ongoing clinical trial and provided rationale for this work, which indicates elraglusib’s potential utility in combination strategies with checkpoint blockade immunotherapy. In patients on this ongoing study, durable clinical responses to single-agent elraglusib have been observed, including in patients with refractory acute T cell leukaemia/lymphoma and malignant gliomas, with a favourable adverse event profile [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…These studies have utilized elraglusib as both a single agent as well as in combination with standard cytotoxic agents [ 23 , 25 ] or BCL-2 and CDK-9 antagonists [ 27 ]. Elraglusib’s clinical activity has also been reported in patients with advanced refractory cancers [ 28 , 29 ]. In the present study, we evaluate elraglusib in vitro and in a B16 melanoma mouse model and compare its efficacy with anti-PD-1 mAb therapy as both a single agent and when combined with PD-1 mAb therapy.…”
Section: Introductionmentioning
confidence: 99%
“…[ 118 ] 9‐ING‐41 selectively inhibits GSK‐3β, thus suppressing cPD‐L1 expression and subsequently exerting excellent in vivo antitumor activity against refractory adult T‐cell leukemia/lymphoma. [ 119 ] Calcium channel blockers, including amlodipine, lercanidipine, and compound F4, can decrease cPD‐L1 expression by reducing the level of cytosolic calcium ion and cleavage of Becklin1 by Calpain, which can improve the efficacy of anti‐PD‐L1 antibodies. [ 106,120 ] Lercanidipine also increases the phosphorylation of STAT1 at Tyr701 and Ser727, inducing the degradation of cPD‐L1.…”
Section: Cpd‐l1 Expression Regulation Mechanisms and Therapeutic Stra...mentioning
confidence: 99%
“…Очевидно, це пов'язано також із здатністю цього цитокіну опосередковано, через дію на клітини впливати на ремоделювання матриксу. Ряд досліджень вказують на здатність IFN-γ індукувати апоптоз [17,18,19], а також координувати не тільки імунну регуляцію, але й проліферацію клітин. [20].…”
Section: гістологічна характеристикаunclassified